Feeding the hungry allies: Canadian food and agriculture during the Second World War - Barker, Stacey J (University of Ottawa (Canada), 2008)
Food is a vital component of modern warfare and during the Second World War Canada used its agricultural capacity to help feed the Allied cause. State direction and the application of new regulatory protocols led to increased production and modified food habits. Canada's food exports increased and farm incomes climbed. Nutritional health was maintained, while economic controls enacted by the Wartime Prices and Trade Board (WPTB) kept Canadian food prices from soaring. The nation's military contributions overshadowed this portion of the Canadian war effort, but food production proved to be a major theme throughout the war and into the peace. Still, feeding the hungry allies was not a painless process. This dissertation examines how the main actors within Canada's food system responded to the exigencies of war in relation to the state policies that sought to maximize the amount of food available. Farmers, hampered by a significantly depleted labour force and lower commodity prices, had to adjust to meet war needs. The war fostered the development of the modern farm lobby in Canada, as the Canadian Federation of Agriculture emerged as a strong campaigner for the nation's farm interests. Consumers enjoyed stable prices but reduced supplies, and experienced a variety of consumption restrictions, including rationing. Called upon to uphold the rules set out by the WPTB, they were enjoined to re-conceptualize food as a communal 'weapon of war' and thus to tailor their eating habits to fit 'patriotic' standards. The majority accepted these codes of behaviour, but obedience co-existed alongside activities such as panic buying, hoarding, and patronizing the black market. This study argues that while Canadians largely accepted and supported wartime food policies, they were also willing to demonstrate their unhappiness with moves that seemed to favour one set of interests over theirs. For the state, navigating this minefield of contending factions was necessary to ensure that Canada's bigger wartime objectives could be realized.
Keywords: History, Canadian.; Economics, Agricultural.